Formation and HPLC analysis of the natural lake pigment obtained from madder (Rubia Tinctoruml.) - (:unkn) unknown (My University, 2010)
In this work, madder lake pigments, aluminium-madder, tin-madder and iron-madder, were obtained by the reaction of KA1(SO4) 2.12H2O, FeSO4.7H2O and SnCl 2.2H2O solutions with madder. High performance liquid chromatography (HPLC) with diode-array detection (DAD) method was utilized for the identification of the lake pigments. Reversed-phase HPLC with diode-array UV-Vis spectrophotometric detection was used in this identification. The extraction of dyestuffs from the lake pigments was carried out with HC1 / methanol / water (2:1:1; v/v/v) solution. From the results of the HPLC analysis of the madder lake pigments, it was determined that the alizarin present in the lake pigments was precipitated by Al(III), Fe(II) and Sn(II).
Keywords: Alizarin; Anthraquinone; Dyestuff; HPLC; Madder; Pigment